Nadaraya-Watson Estimator a Smoothing Technique for Estimating Regression Function - رشيد, ظافر حسين; حمود, مناف يوسف (Journal of Economics and Administrative Sciences, 2012)
The using of the parametric models and the subsequent estimation methods require the presence of many of the primary conditions to be met by those models to represent the population under study adequately, these prompting researchers to search for more flexible models of parametric models and these models were nonparametric models.    In this manuscript were compared to the so-called Nadaraya-Watson estimator in two cases (use of fixed bandwidth and variable) through simulation with different models and samples sizes.  Through simulation experiments and the results showed that for the first and second models preferred NW with fixed bandwidth for all cases, whether for the third model the results showed a preference NW estimator with variable bandwidth.